Extending intervention window from 1000 to 8000 first day of life: how can it boost the stunting reduction program? - Sutiari, Ni Ketut; Adhi , Kadek Tresna; Utami, Ni Wayan Arya; Astuti, Putu Ayu Swandewi (Universitas Udayana, 2024)
Stunting is one of the triple malnutrition burdens in Indonesia, beside obesity and micronutrient deficiency. Stunting is a reflection of long-term undernourishment which resulted in stunted growth. National Health Survey Data showed the reduction of stunting rate among under-five children in Indonesia from 37.2% in 2013 to 30.4% in 2018 and 21.5% in 2023. Despite this decreasing trend, the national stunting rate was still above the World Health Organization threshold of 20%. There is also a wide discrepancy between provinces in Indonesia with stunting rate ranges from 7.2% in Bali to 39.2% in Papua. Back in 2011, there was a movement by 28 countries including Indonesia regarding the 1000 first day of life (1000-days) program. This was an approach targeting children during their 1000 first day of life through specific and sensitive nutritional interventions. The 1000-days is started during pregnancy until the child is two years old. This movement involved related stakeholders from national and sub-national level including ministries, community organization, private sectors, professional organization, academics and others.